2023
DOI: 10.1101/2023.03.08.531671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ancIBD - Screening for identity by descent segments in human ancient DNA

Abstract: Long DNA sequences shared between two individuals, known as Identical by descent (IBD) segments, are a powerful signal for identifying close and distant biological relatives because they only arise when the pair shares a recent common ancestor. Existing methods to call IBD segments between present-day genomes cannot be straightforwardly applied to ancient DNA data (aDNA) due to typically low coverage and high genotyping error rates. We present ancIBD, a method to identify IBD segments for human aDNA data imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…3B) that persists for at least 1.500 years and transcends the linguistic boundaries identified by classical authors (7,9). Our findings are further reinforced by IBD-sharing between certain samples from Albania and North Macedonia (Table S20) (50).…”
Section: The Establishment Of the Ba-ia Balkan Genetic Clinesupporting
confidence: 80%
See 1 more Smart Citation
“…3B) that persists for at least 1.500 years and transcends the linguistic boundaries identified by classical authors (7,9). Our findings are further reinforced by IBD-sharing between certain samples from Albania and North Macedonia (Table S20) (50).…”
Section: The Establishment Of the Ba-ia Balkan Genetic Clinesupporting
confidence: 80%
“…To gain insight into the biological and linguistic origins of modern Albanians, we undertake a palaeogenomic transect of the Balkans from the Neolithic to the modern era (Fig. 1; Tables S1-S2), using more than 6000 previously published ancient genomes from western Eurasia, which we interrogate by means of state-of-the-art statistical analyses (Tables S3-S18), large-scale algorithms that quantify human mobility (Table S19), and a meta-analysis of ancient IBD-sharing data [Tables 20-21; (50)]. We also mine publicly available Y-chromosome haplogroup data from more than 2500 ancient and modern Balkan samples (Tables S22-S34), which reveal the proximate ancestors of modern Albanian men.…”
Section: Introductionmentioning
confidence: 99%
“…BOO samples were imputed and phased using GLIMPSE 32 following the default parameters, and merged with already published data, in order to test for patterns of IBD sharing among the individuals using ancIBD 34 . IBD analyses were restricted to samples covering more than 600K SNPs with GP>=0.99 after genotype imputation.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that with dense ancient DNA sampling, at sufficient sequencing depth for imputation (∼0.1X for whole genomes), the detection of fine scale population structure in closely related ancient populations is possible 58–60 . To investigate the spread and diversification of Germanic-speaking populations, we sequenced 710 ancient genomes (Table, Supplementary Note S1A and S1B) from human populations across western Eurasia, with a focus on the northern European Iron Age and the bordering Celtic-speaking region of western Europe (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Migrations within Europe over the last 5,000 years would have represented interactions by much more closely related populations than the arrival of the Neolithic Farmers and Bronze Age Steppe Pastoralists, limiting the possibility of their detection in ancient DNA studies. Recent studies have shown that with dense ancient DNA sampling, at sufficient sequencing depth for imputation (~0.1X for whole genomes), the detection of fine scale population structure in closely related ancient populations is possible [58][59][60] . To investigate the spread and diversification of Germanic-speaking populations, we sequenced 710 ancient genomes (Table , Supplementary Note S1A and S1B) from human populations across western Eurasia, with a focus on the northern European Iron Age and the bordering Celtic-speaking region of western Europe (Figure 1).…”
mentioning
confidence: 99%